2011
DOI: 10.1186/1749-8104-6-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of melanopsin-based irradiance detecting circuitry

Abstract: BackgroundMost retinal ganglion cells (RGCs) convey contrast and motion information to visual brain centers. Approximately 2% of RGCs are intrinsically photosensitive (ipRGCs), express melanopsin and are necessary for light to modulate specific physiological processes in mice. The ipRGCs directly target the suprachiasmatic nucleus (SCN) to photoentrain circadian rhythms, and the olivary pretectal nucleus (OPN) to mediate the pupillary light response. How and when this ipRGC circuitry develops is unknown.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(91 citation statements)
references
References 37 publications
7
83
0
1
Order By: Relevance
“…We propose that the targeting of the ipsilateral SCN by the contralateral ipRGCs occurs later in development when the robo1-slit or analogous repulsive signals have been down-regulated. Consistent with this idea, the SCN is fully innervated by retinal fibers only ∼10 d after birth (40).…”
Section: Discussionsupporting
confidence: 66%
“…We propose that the targeting of the ipsilateral SCN by the contralateral ipRGCs occurs later in development when the robo1-slit or analogous repulsive signals have been down-regulated. Consistent with this idea, the SCN is fully innervated by retinal fibers only ∼10 d after birth (40).…”
Section: Discussionsupporting
confidence: 66%
“…Whereas all SCN neurons are GABAergic, the shell and the core subdivisions show, respectively, localized expression of arginine vasopressin (AVP) or vasoactive intestinal peptide (VIP), and gastrin-releasing peptide (GRP). Anatomical studies have shown that the SCN is densely innervated by retinal axonal projections (Hattar et al 2006;McNeill et al 2011), the core subdivision being the principal site of direct and indirect retinal innervation. The discovery that light-mediated resetting of the SCN clock was accompanied by the induced expression of immediate-early genes such as cfos in the retinorecipient core directed the analysis of circadian timekeeping in mammals toward signal transduction and transcriptional regulation.…”
Section: A Brief Timeline Of the Scn Clockmentioning
confidence: 99%
“…38 The ablation of all Brn3b-positive M1-M5 pRGCs was also shown to disrupt the PLR, yet, given the widespread loss of pRGC subtypes using this approach, it is not possible to conclude from this study which class of pRGC mediates the PLR or other behaviours. However, the timeline with which M1 cells innervate the shell of the OPN coincides with the development of the PLR, 37 and the selective ablation of M1-type pRGCs has been shown to severely impair the PLR. 47 Therefore it would seem that the PLR is driven by M1-type pRGCs, and thus distinct subsets of M1-type pRGCs are responsible for driving circadian entrainment and the PLR.…”
Section: Physiological Roles Performed By Prgc Subtypesmentioning
confidence: 99%
“…To date at least five distinct subtypes of pRGC have been identified, termed M1-M5-type pRGCs. 1,2,[32][33][34][35] These cells show differences in morphology and retinal connections, and exhibit light responses with markedly different kinetics and sensitivities ( Figure 1b) [32][33][34][37][38][39] (Figure 1c), and would therefore seem to be tasked with performing different physiological roles (for review see Schmidt et al 36,40 ). However, the innervations of each class of pRGC are only partially resolved, and the specific roles performed by each class of pRGC are yet to be fully determined.…”
Section: Subtypes Of Prgcmentioning
confidence: 99%
See 1 more Smart Citation